Creativity to Innovation: What Lesson Learned from Digital Transformation in Financial Accountability in Government Practices - Ariesmansyah, Andre; Lestari, Anggun Hilendri; Yodiansyah, Hefri; Chakim, Mochamad Heru Riza; Junaedi, I Wayan Ruspendi (Budapest International Research and Critics University, 2021)
This work is expected to gain a top-down understanding of various evidence of past logical investigations to understand how imagination drives government development in completing the capacity to serve the general public, especially the monetary sector, by utilizing innovation. The information we obtain relies on logical examination, beforehand from various sources of literature both at home and abroad that discuss how financial administration in the bookkeeping technology includes the use of the latest innovations. In addressing this question, of course, we directed the first informational review through a top-down assessment of the coding framework, evaluation data and completed it after the point of responding to legitimate and valid questions. This review depends on the data examined from different correspondence publications, and we report it as a qualitative report that describes utilizing investigation of inside and outside publication journals to deal with answering problems. In this review, we get results, including information through electronic investigations, that government creativity using digital applications for public financial services has turned to transparent and modern prime service innovations. Thus, this result becomes an essential input for improving public services in the country.